Direct engulfment of synapses by overactivated microglia due to cadmium exposure and the protective role of Nrf2 - Siyao Li; Mingdan You; Chengjie Chen; Jingqi Fu; Yuanyuan Xu; Jingbo Pi; Yi Wang (Ecotoxicology and Environmental Safety)
Cadmium (Cd), a notorious environmental pollutant, has been linked to neurological disorders, but the underlying mechanism remains elusive. We aimed to explore the role of microglia in Cd-induced synaptic damages at environmentally relevant doses and whether microglia directly engulf synaptic structures. Nrf2 is deeply implicated in the status of microglial activation; therefore, we also investigated whether it is involved in the above process. Nrf2 knockout mice and wild-type mice were used to explore prolonged Cd exposure-induced synaptic damages, learning-memory impairments, and microglial activation. We also created Nrf2 knockdown (KD) BV2 microglia to investigate the role of cell-specific Nrf2 in Cd-induced microglial activation. Finally, we developed co-culture systems of either Nrf2-KD or Scramble microglia and primary neurons or HT22 neurons to study the effects of Nrf2-regulated microglial activation on synaptic damages induced by Cd. Moreover, the direct engulfment, a main avenue in microglia that may be responsible for Cd-induced synaptic damages and regulated by Nrf2, was specifically studied in vivo and in vitro, along with underlying specific mechanisms. We found that Cd exposure induced microglial overactivation, and Cd-overactivated microglia impaired synapses through direct engulfment of synaptic structures, which may contribute to learning-memory impairments. Both fractalkine and complement pathways underlay microglial engulfment of synapses due to Cd exposure. Nrf2 was essential in preventing microglial overactivation and subsequent direct engulfment, thus preventing the consequent synaptic damages due to Cd exposure. Overall, the findings suggest that Cd-overactivated microglia damage synapses through direct engulfment, resulting from the activation of fractalkine and complement pathways.